2003
DOI: 10.1177/014556130308201014
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriologic findings in Patients with Chronic Sinusitis

Abstract: We studied the bacteriology ofmaxillary sinus aspirates obtain ed from patients diagnosed with chronic sinusitis. We recovered 659 strains from 510 aspirates; of these, 572 (86.8 %) were aerobes and 87 (13.2 %) were anaerobes. Aerobes only were recovered from 310 of the 510 specimens (60.8%) and anaerobes only from 31 (6.1 %). Among the 572 aerobic bacteria, the most prevalent organisms were Streptococcus viridans (158 strains [27.6%]), Streptococcus pneumoniae (67 [11 .7 %}), Corynebacterium species (66 [11 .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…1 However, in our present study, we used S. pneumoniae instead of Bacteroides fragilis, because S. pneumoniae is the predominant organism in the cultures of maxillary sinus aspirates obtained from patients diagnosed with CRS. 7 Although Jacob et al observed obvious histological changes in his model, the 4-week study duration is not in accordance with the current definition of human CRS. 1 Our study showed a 12-week intervention, which fit the definition of human CRS, and provoked more persistent and severe pathological changes of CRS than a 4-week intervention.…”
Section: Discussionmentioning
confidence: 76%
“…1 However, in our present study, we used S. pneumoniae instead of Bacteroides fragilis, because S. pneumoniae is the predominant organism in the cultures of maxillary sinus aspirates obtained from patients diagnosed with CRS. 7 Although Jacob et al observed obvious histological changes in his model, the 4-week study duration is not in accordance with the current definition of human CRS. 1 Our study showed a 12-week intervention, which fit the definition of human CRS, and provoked more persistent and severe pathological changes of CRS than a 4-week intervention.…”
Section: Discussionmentioning
confidence: 76%
“…coli , Peptostreptococcus sp, Klebsiella sp, and Fusobacterium are also seen in lower abundance. 39 , 40 , 41 , 42 , 43 However, with the exception of S . aureus , the association between any single species and CRS is tenuous.…”
Section: Chronic Rhinosinusitis and Microbiomementioning
confidence: 99%
“…[17][18][19][20] Coagulase-negative staphylococci are frequently isolated, but it is not clear whether these represent true causative bacteria. …”
Section: Microbiologymentioning
confidence: 99%